Exploring the Use of Feminist Therapy Concepts in Counselling Malaysian Chinese Women - Chong, Pit Fong (1999)
The purpose of this study is to examine the role of feminist therapy in empowering women in the Malaysian Chinese community. This study is divided into two parts. First, to examine feminist therapy philosophical assumptions, problem conceptualizations and intervention strategies, elements differentiating feminist therapy from conventional counseling and possibilities of reconciliation the two are also examined. Second, applicability of feminist therapy in Malaysian Chinese community is also studied. In addition, effects of sex-role stereotypes and related gendered beliefs affecting women in the Chinese community are also explored. Content analysis on twelve cases by a counselor from Red Dust Counseling center was used in this research to identify themes of feminist therapy and also to examine how power relations and sex-role stereotypes could be employed to conceptualize clients' problems.